The ‘Valley of Ashes’ and the ‘Fresh Green Breast’: Metaphors from The Great Gatsby in planning New York - Lieven Ameel (United Kingdom, 2022)
Visions in planning of what a city could or should be tend to be constructed around metaphors, rhetorical tropes that crystalize the image of a preferable future city. Such metaphorizations are never innocent: they draw on pre-existing cultural narratives and activate particular frames of expectation. This article examines two metaphors used in the planning of New York City, and its shores, in particular: the spectre of the ‘valley of ashes’ and the dream of the ‘fresh green breast’. These metaphors, taken from F. Scott Fizgerald’s novel The Great Gatsby (1925), appear time and again in the planning and thinking of the New York shoreline, from Robert Moses’s plans for Flushing Meadow to Major Bloomberg’s waterfront development and Eric Sanderson’s vision of a 2406 New York in Mannahatta (2006). This article examines how the metaphors of the ‘valley of ashes’ and the ‘fresh green breast’ have been adapted throughout decades of planning New York City to accommodate changing relationships, conflicts and ideals, always infused by a pastoral undercurrent that is already questioned in Fitzgerald’s novel.